Novelty and Creativity. - Gilliland, Rex (2009)
Keywords: dept.phi; faculty_collection

Education in the Global Knowledge Society. - Gorniak, Krystyna (2007)
Keywords: dept.phi; faculty_collection; sabbatical_report

Creating Two Book Manuscripts. - Bynum, Terrell (2001)
Keywords: dept.phi; faculty_collection; sabbatical_report

Writing Two Major Chapters of a Book on Flourishing Ethics: Sabbatical Spring 2009 - Bynum, Terrell Ward (2009)
The chapter on the information ethics of Oxford scholar, Luciano Floridi, was completed and is scheduled for publication in Floridi's anthology. The keynote address, Philosophy and the Information Revolution, presented at the Computer Ethics: Philosophical Enquiry 2009 conference in Corfu, Greece, is also scheduled for publication in the journal Ethics and Information Technology. The ideas from both articles have been included in the curriculum for the Computer Ethics class at SCSU.
Keywords: dept.phi; faculty_collection

French Interpretations of Heidegger: An Exceptional Reception - Pettigrew, David; Raffoul, François (State University of New York Press, 2008)
"French Interpretations of Heidegger undertakes a philosophical engagement with the work of the most significant and creative figures involved in the reception of Heidegger in France. The essays address those thinkers who have been influenced by Heidegger's thought and have interpreted it in remarkable ways, including Levinas, Beaufret, Sartre, Merleau-Ponty, Foucault, Derrida, Deleuze, Nancy, Lacoue-Labarthe, Irigaray, Zarader, Greisch, and Dastur. The volume explores the extraordinary impact that Heidegger's thought has had on contemporary French philosophy, including such movements as existentialism, deconstruction, feminist theory, post-structuralism, and hermeneutics, and illustrates its impact on the American continental scene as well."–Jacket.
Keywords: Heidegger; Martin; 1889-1976; Philosophy; French; dept.phi; faculty_collection

Genocide's Aftermath: Responsibility and Repair - Card, Claudia; Marsoobian, Armen (Blackwell Pub., 2007)
Keywords: Genocide; Government policy; Genocide; History; Genocide; Moral and ethical aspects; Genocide; Prevention; dept.phi; faculty_collection

The Creation of the World, or, Globalization - Nancy, Jean-Luc (State University of New York Press, 2007)
"Appearing in English for the first time, Jean-Luc Nancy's 2002 book reflects on globalization and its impact on our being-in-the-world. Developing a contrast in the French language between two terms that are usually synonymous, or that are used interchangeably, namely globalisation (globalization) and mondialisation (world-forming), Nancy undertakes a rethinking of what "world-forming" might mean. At stake in this distinction is for him nothing less than two possible destinies of our humanity, and of our time. This book is an important contribution by Nancy to a philosophical reflection on the phenomenon of globalization and a further development on his earlier works on our being-in-common, justice, and a-theological existence."–Jacket.
Keywords: Globalization; Philosophy; Political science; Philosophy; Teleology; dept.phi; faculty_collection

The Philosophical Challenge of September 11 - Rockmore, Tom; Margolis, Joseph; Marsoobian, Armen (Blackwell Pub., 2005)
Keywords: Philosophy; Philosophy; Political science; September 11 Terrorist Attacks; 2001; Terrorism; United States; Terrorism; dept.phi; faculty_collection

Computer Ethics and Professional Responsibility - Bynum, Terrell Ward; Rogerson, Simon (Blackwell Pub., 2004)
Keywords: Electronic data processing; Moral and ethical aspects; dept.phi; faculty_collection

The Blackwell Guide to American Philosophy - Marsoobian, Armen; Ryder, John (Blackwell Pub., 2004)
Keywords: Philosophy; American; dept.phi; faculty_collection

The Book of Love and Pain: Thinking at the Limit with Freud and Lacan - Nasio, Juan-David (State University of New York Press, 2004)
"In The Book of Love and Pain, Juan-David Nasio offers the first exclusive treatment of psychic pain in Freudian and Lacanian psychoanalytic literature. Using insights gained from more than three decades as a practicing psychoanalyst, Nasio addresses the limits faced by the analyst in attempting to think and treat pain psychoanalytically. He suggests that while pain is about separation and loss, psychic pain is intensified by paradoxical overinvestment in the lost loved one. Included are discussions of the pain of mourning, the pain of jouissance, unconscious pain, pain as an object of the drive, pain as a form of sexuality, pain and the scream, and the pain of silence. In offering a phenomenological description of psychic pain, The Book of Love and Pain fills a gaping void in psychoanalytic research and will play an important role in our understanding of the human psyche. Book jacket."–Jacket.
Keywords: Pain; Psychological aspects; Psychoanalysis; Stress; Psychological; dept.phi; faculty_collection; methods; psychology; Psychoanalytic Theory; Psychoanalytic Therapy; therapy; Bereavement; Pain

Cyberphilosophy: The Intersection of Philosophy and Computing - Moor, James H.; Bynum, Terrell Ward (Blackwell, 2002)
Keywords: Data processing; Philosophy; dept.phi; faculty_collection

Heidegger and Practical Philosophy - Raffoul, François; Pettigrew, David (State University of New York Press, 2002)
Investigating the extent to which Heidegger's thought can be read as a crucial resource for practical philosophy and the articulation of an ethos for our time, leading scholars offer a sustained and intensive focus on Heidegger's thought of praxis.–(Source of description unspecified.)
Keywords: Heidegger; Martin; 1889-1976; Ethics; Political science; Philosophy; Practice (Philosophy); dept.phi; faculty_collection

Ethics and Information Technology: Guest editor's introduction - Bynum, T.W. (Ethics and Information Technology, 2001)
0 citations (Crossref) [2023-10-31]
Keywords: Information technology; Social sciences; dept.phi

Transformation in Deleuze and Heidegger: Serial and thematic repetition - Gilliland, R. (Philosophy Today, 2005)
4 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Probability and Tempered Modal Eliminativism - Shaffer, M.J. (History and Philosophy of Logic, 2004)
In this paper the strategy for the eliminative reduction of the alethic modalities suggested by John Venn is outlined and it is shown to anticipate certain related contemporary empiricistic and nominalistic projects. Venn attempted to reduce the alethic modalities to probabilities, and thus suggested a promising solution to the nagging issue of the inclusion of modal statements in empiricistic philosophical systems. However, despite the promise that this suggestion held for laying the ‘ghost of modality’ to rest, this general approach, tempered modal eliminativism, is shown to be inadequate for that task. © 2004 Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Daniel Dennett and the computational turn - Dorbolo, J.; Barnette, R.; Bynum, T.; Cavalier, R.; Moor, J.; Rosenthal, D.M.; Uzgalis, B. (Minds and Machines, 2006)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Norbert wiener and the rise of information ethics - Bynum, T.W. (Information Technology and Moral Philosophy, 2008)
To live effectively is to live with adequate information. Thus, communication and control belong to the essence of man's inner life, even as they belong to his life in society. Norbert Wiener SCIENCE, TECHNOLOGY, AND ETHICS. Major scientific and technological innovations often have profound social and ethical effects. For example, in Europe during the sixteenth and seventeenth centuries, Copernicus, Newton, and other scientists developed a powerful new model of the universe. This stunning scientific achievement led to increased respect for science and for the power of human reasoning. During that same era, recently invented printing-press technology made it possible to spread knowledge far and wide across Europe, instead of leaving it, as before, in the hands of a privileged minority of scholars. Inspired by these scientific and technological achievements, philosophers, such as Hobbes, Locke, and Rousseau, re-examined human nature and the idea of a good society. They viewed human beings asrational agentscapable of thinking for themselves and acquiring knowledge through science and books. In addition, they interpreted society as a creation of informed, rational citizens working together throughsocial contracts. These philosophical developments laid foundations for ethical theories such as those of Bentham and Kant, and for political changes such as the American Revolution and the French Revolution. Today, after far-reaching scientific achievements in physics, biology, and cybernetics – and after recent technological advances in digital computing and information networks – philosophers are again rethinking the nature of human beings and of society. © Cambridge University Press 2008 and 2009.
Journal Abbreviation: Information Technology and Moral Philosophy
Keywords: dept.phi

Response to Frisina's response - Yang, X. (Dao, 2009)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi; peer-reviewed

Guest Editor's introduction. - Bynum, Terrell (Ethics and Information Technology, 2001)
Place: (C)2001 Kluwer Academic Publishers
Keywords: dept.phi; ❓ Multiple DOI

Ethical challenges to citizens of ‘The automatic Age’: Norbert Wiener on the information society - Bynum, Terrell Ward (Journal of Information, Communication and Ethics in Society, 2004)
This article discusses the foresight of philosopher/mathematician Norbert Wiener who, in the 1940s, founded Information Ethics as a research discipline. Wiener envisioned the coming of an “automatic age” in which information technology would have profound social and ethical impacts upon the world. He predicted, for example, machines that will learn, reason and play games; “automatic factories” that will replace assembly-line workers and middle managers with computerized devices; workers who will perform their jobs over great distances with the aid of new communication technologies; and people who will gain remarkable powers by adding computerized “prostheses” to their bodies. To analyze the ethical implications of such developments, Wiener presented some principles of justice and employed a powerful practical method of ethical analysis. © 2004, Emerald Group Publishing Limited
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/069-878-157-439-708 tex.type: [object Object]
Keywords: Human purposes; Information ethics; Justice; dept.phi; peer-reviewed

Privacy as life, liberty, property - Volkman, Richard (Ethics and Information Technology, 2003)
The cluster of concerns usually identified as matters of privacy can be adequately accounted for by unpacking our natural rights to life, liberty, and property. Privacy as derived from fundamental natural rights to life, liberty, and property encompasses the advantages of the control and restricted access theories without their attendant difficulties., (C)2003 Kluwer Academic Publishers
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-294-459-957-177 tex.type: [object Object]
Keywords: Access control; Data privacy; Information technology; Judith Thomson; Natural rights; Privacy; Right to privacies; Right to privacy; Social sciences; Thomson; dept.phi; natural rights; privacy; right to privacy

Introduction to cyberphilosophy - Moor, James H.; Bynum, Terrell Ward (Metaphilosophy, 2002)
9 citations (Crossref) [2023-10-31] Citation Key Alias: pop00167 tex.type: [object Object]
Keywords: dept.phi

Computer ethics: Its birth and its future - Bynum, Terrell Ward (Ethics and Information Technology, 2001)
This article discusses some "historical milestones" in computer ethics, as well as two alternative visions of the future of computer ethics. Topics include the impressive foundation for computer ethics laid down by Norbert Wiener in the 1940s and early 1950s; the pioneering efforts of Donn Parker, Joseph Weizenbaum and Walter Maner in the 1970s; Krystyna Gorniak's hypothesis that computer ethics will evolve into "global ethics"; and Deborah Johnson's speculation that computer ethics may someday "disappear"., (C)2001 Kluwer Academic Publishers
23 citations (Crossref) [2023-10-31] Place: (C)2001 Kluwer Academic Publishers Publisher: Department of Philosophy, Southern Connecticut State University, New Haven, CT 06515 USA E-mail: computer.ethics@home.com or bynum@southernct.edu
Keywords: Applied ethics; Computer ethics; Cybernetics; Global ethics; Information ethics; Information technology; Philosophical aspects; Professional responsibilities; Professional responsibility; Social sciences; applied ethics; computer ethics; cybernetics; dept.phi; global ethics; information ethics; professional responsibility; ❓ Multiple DOI

The challenge of applying ethics. - Bynum, Terrell Ward (Science and Engineering Ethics, 2001)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-089-426-976-197 tex.type: [object Object]
Keywords: *Computers; *Ethics; Computers; Ethics; Humans; article; computer; dept.phi; ethics; human

Revolution and the library - Gorniak-Kocikowska, K (Library Trends, 2001)
The focus of this article is primarily on the impact that the computer revolution has on college/university libraries, although many of the issues discussed here are relevant to other types of libraries as well. The university library in its present form is a product of the printing press revolution. In all likelihood, the computer revolution will have an even more profound impact on the library than did the printing press revolution.
tex.unique-id: ISI:000168596400006
Keywords: dept.phi; ⛔ No DOI found

Special section on computer ethics - Bynum, Terrell Ward (Science and Engineering Ethics, 2000)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/029-516-067-899-015 tex.type: [object Object]
Keywords: dept.phi

The foundation of computer ethics - Bynum, Terrell Ward (ACM Sigcas Computers and Society, 2000)
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-474-501-231-720 tex.type: [object Object]
Keywords: dept.phi

Milestones in the History of Information and Computer Ethics - Bynum, Terrell Ward (The Handbook of Information and Computer Ethics, 2009)
This chapter contains sections titled: Introduction Norbert Wiener's Foundation of Information Ethics Computer Ethics Developments after Wiener and before Maner Walter Maner's Computer Ethics Initiative Deborah Johnson's Influential Textbook and the Start of the “Uniqueness Debate” James Moor's Classic Paper and His Influential Computer Ethics Theory The Professional-Ethics Approach of Donald Gotterbarn Computing and Human Values Luciano Floridi's Information Ethics Theory Concluding Remarks: The Exponential Growth of Computer Ethics References and Selected Resources
Keywords: Computer ethics developments - after Wiener and before Maner; Donald Gotterbarn professional-ethics approach; Information and computer ethics - milestones in history; computer ethics developments - after Wiener and before Maner; dept.phi; information and computer ethics - milestones in history

Federative Global Democracy - Cavallero, Eric (Metaphilosophy, 2009)
Abstract: In this essay a set of principles is defended that yields a determinate allocation of sovereign competences across a global system of territorially nested jurisdictions. All local sovereign competences are constrained by a universal, justiciable human rights regime that also incorporates a conception of cross-border distributive justice and regulates the competence to control immigration for a given territory. Subject to human rights constraints, sovereign competences are allocated according to a conception of global democracy. The proposed allocation scheme can accommodate substantial local autonomy while at the same time ensuring that everyone has a voice in the political decisions that affect his or her interests. The relevant class of affected interests is fully specified. Relevant affects are of two kinds: those that impose norms of governance on individuals, and those that impose external costs on them. The favored sense of “an external cost” is developed and defended.
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/151-680-891-324-807, pop00258 tex.type: [object Object]
Keywords: Affected interests; All-affected principle; Borders; Confederalism; Democracy; Democratic deficit; Equal protection; External costs; Externalities; Federalism; Global governance; Global justice; Globalization; Human rights; Immigration; International law; affected interests; all-affected principle; borders; confederalism; democracy; democratic deficit; dept.phi; equal protection; external costs; externalities; federalism; global governance; global justice; globalization; human rights; immigration; international law; nationalism; sovereignty; territoriality

Acknowledging intergenerational moral responsibility in the aftermath of genocide - Marsoobian, Armen T (Genocide Studies and Prevention, 2009)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/023-944-111-369-330 tex.type: [object Object]
Keywords: dept.phi

How to make sense of the claim “True knowledge is what constitutes action”: A new interpretation of wang yangming’s doctrine of unity of knowledge and action - Yang, Xiaomei (Dao-a Journal of Comparative Philosophy, 2009)
No one denies the importance of applying knowledge to actions. But claiming identity (unity) of knowledge and action is quite another thing. There seem to be two problems with the claim: (1) the identity claim implies that the sole cause for one to fail to act on what one judges to be right is ignorance, but it is obviously false that the sole cause of failure in moral actions is ignorance. (2) The identity statement implies non-separation of knowledge and action. But knowledge does not necessarily lead to action. However, the identity of knowledge and action is what a famous Ming Confucian scholar, Wang Yang-ming, proposed and the concept became the central doctrine of his teaching. Though there are several major interpretations of Wang's doctrine in contemporary literature, it is not clear to me how they deal with the above mentioned difficulties. In this article, I will discuss these interpretations of the doctrine and propose a new interpretation. My purpose is to give an interpretation of Wang's doctrine that has the capacity of dealing with these challenges to the doctrine and also captures the essence of his teaching. © 2009 Springer Science+Business Media B.V.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-501-215-892-486 tex.type: [object Object]
Keywords: Action; Chinese philosophy; Moral knowledge (liang zhi); Neo-confucianism; dept.phi; peer-reviewed

ICT and the tension between old and new: the human factor - Gorniak-Kocikowska, Krystyna (Journal of Information, Communication and Ethics in Society, 2008)
Purpose The purpose of this paper is to deepen the understanding of tensions between old and new in the emerging global society driven by information and communication technology (ICT); and to argue that creation of a theory of this society would contribute in the easing of these tensions. Design/methodology/approach The methods used in this paper are mostly analytical, descriptive, and qualitative. An analysis of the creation and development of ICT from a mathematical discipline of computer science to a universal tool and a driving force of the emerging global society, a development which is paralleled by the commercialization of ICT, is followed by two case studies illustrating the tensions between old and new and the role ICT plays in them. One case is centered on the challenges of traditional models of education by new, ICT-friendly approaches, like the Multiple Intelligences Theory; the other addresses tensions between old and new that in many societies presently take the form of tensions between local/national and global. Findings A claim is formed that the existing tensions between old and new are closely linked to the tensions between the two most common forms of society, inclusive (egalitarian) and exclusive (elitist). Originality/value The paper will help understand some of the reactions to the process of globalization. It can serve as a tool for assessment and prediction regarding this process. Lastly, the paper contains a justification of merit in the creation of a “grass root” theory of an ICT-driven global society built on a universally accepted ethical foundation. © 2008, Emerald Group Publishing Limited
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00314 tex.type: [object Object]
Keywords: Communication technologies; Education; Ethics; Globalization; Information society; Language; dept.phi; peer-reviewed

Some issues in Chinese philosophy of religion - Yang, Xiaomei (Philosophy Compass, 2008)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/098-851-894-499-307 tex.type: [object Object]
Keywords: dept.phi

Casuistry and computer ethics - Coleman, Kari Gwen (Metaphilosophy, 2007)
At the heart of the uniqueness debate is the possibility that the computer revolution may demand more in the way of ethical analysis than our traditional (that is, modern) ethical edification has prepared us for. In short, it may present new and unique problems and therefore demand new and unique solutions. In this article I argue that the solution is in fact an old and not-sounique one: casuistry. Appealing to Jonsen and Toulmin's analysis of casuistry (1988), I argue that a casuistic methodology is a more accurate description of the moral reasoning used by contemporary computer ethicists than are other accounts. In addition, I argue that the strengths that enabled casuistry to deal successfully with radical social, economic, and religious changes in the sixteenth and seventeenth centuries render casuistry well suited to the task of dealing with radically new situations like those found in twentieth- and twenty-first-century computer technology. Before concluding, I briefly explore Pascal's fatal critique of casuistry and its relevance for contemporary computer ethics. © 2007 Metaphilosophy LLC and Blackwell Publishing Ltd.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-786-839-279-000 tex.type: [object Object]
Keywords: Casuistry; Computer ethics; Information ethics; Methodology; Moral reasoning; Uniqueness debate; dept.phi

From computer ethics to the ethics of global ICT society - Gorniak-Kocikowska, Krystyna (Library Hi Tech, 2007)
Purpose - The purpose of this paper is to address the place of computer/ICT ethics in the global ICT society driven by knowledge economy. Design/methodology/approach - The paper focuses on three main issues: the evolution of the name of the leading technology of our times and, accordingly, the evolution of the name of the society in which this technology plays the leading role; some ethical dilemmas that the global ICT society will need to solve; global ICT ethics and the knowledge economy. Findings - The paper suggests that global ICT ethics should be an ethics focusing on the dynamics of the relationship between the weak and the strong, the rich and the poor, the healthy and the sick worldwide - and it should explore the ethical problems from the point of view of both parties involved. That way, Global ICT Ethics can have a truly communicative character, and it can become an ethics that will be both a co-creator and also a result of a democratic processes. Originality/value - This paper should interest anyone concerned with ICT and globalization.
15 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/047-860-005-442-947 tex.unique-id: [object Object]
Keywords: Communication technologies; Ethics; Globalization; dept.phi; peer-reviewed

Flourishing ethics - Bynum, Terrell Ward (Ethics and Information Technology, 2006)
This essay describes a new ethical theory that has begun to coalesce from the works of several scholars in the international computer ethics community. I call the new theory Flourishing Ethics because of its Aristotelian roots, though it also includes ideas suggestive of Taoism and Buddhism. In spite of its roots in ancient ethical theories, Flourishing Ethics is informed and grounded by recent scientific insights into the nature of living things, human nature and the fundamental nature of the universe-ideas from today's information theory, astrophysics and genetics. Flourishing Ethics can be divided conveniently into two parts. The first part, which I call Human-Centered FE, is focused exclusively upon human beings - their actions, values and characters. The second part, which I call General FE, applies to every physical entity in the universe, including humans. Rather than replacing traditional great ethical theories, Flourishing Ethics is likely to deepen and broaden our understanding of them. © Springer Science+Business Media B.V. 2006.
59 citations (Crossref) [2023-10-31] Citation Key Alias: pop00043
Keywords: Aristotelian ethics; Astrophysics; Computer ethics; Cybernetics; Cyborg ethics; Entropy; Good and evil; Information ethics; Infosphere; Just consequentialism; Philosophical aspects; Robot ethics; dept.phi

Introduction: genocide's aftermath - Card, Claudia; Marsoobian, Armen T (Metaphilosophy, 2006)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/017-589-143-645-589 tex.type: [object Object]
Keywords: dept.phi

Dynamic traditions: why globalization does not mean homogenization - Volkman, Richard (Journal of Information, Communication and Ethics in Society, 2006)
In light of the relation between culture and markets, an analysis of cultural evolution reveals that globalization will not lead to the homogenization of world cultures. © 2006, Emerald Group Publishing Limited
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/043-392-929-789-895 tex.type: [object Object]
Keywords: Culture; Globalization; Market; Tradition; dept.phi; peer-reviewed